PENGARUH RISIKO BISNIS, RISIKO KEUANGAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN HOTEL, RESTORAN, DAN PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Marlim B1021161021, Desisca Indah (Jurnal Manajemen Update, 2020)
The development of hotel, restaurant, and tourism companies today is so rapid that hotel, restaurant and tourism companies must make appropriate policies in accordance with the strategy that has been designed to achieve the company's goals, namely to achieve predetermined profitability targets. But only companies that have good financial management and performance are able to survive in today's tight business world. This study wants to reveal how business risk, financial risk and company growth in hotel, restaurant and tourism companies on the Indonesia Stock Exchange (IDX) compete to produce the desired financial performance in this developing era, where every large or small company wants a big profit.This study uses secondary data from 21 samples of financial statements of hotel, restaurant, and tourism companies and sampling using purposive sampling techniques. The classic assumption test in this study includes normality test, multicollinearity, heteroscedasticity test, autocorrelation test. Data analysis using multiple linear regression analysis, coefficient of determination test, t-test, and f-test. Data analysis using multiple linear regression analysis with SPSS 22.The results showed that the business risk variable partially (t test) had no significant effect on the financial performance of hotel, restaurant and tourism companies on the Indonesia Stock Exchange (IDX); partial financial risk variable (t test) significant negative fan effect on financial performance in hotel, restaurant and tourism companies on the Indonesia Stock Exchange (IDX); while the company's growth variable has a positive and significant effect on financial performance in hotel, restaurant and tourism companies on the Indonesia Stock Exchange (IDX). The results of the simultaneous study (f test) showed a significant and positive influence on the variables of business risk, financial risk and company growth on financial performance in hotel, restaurant and tourism companies on the Indonesia Stock Exchange (IDX).Keywords: Business Risk, Financial Risk, Company Growth, and Financial Performance.Daftar PustakaAbor, J. (2006). The Effect Of Capital Structure On Profitability: An Empirical Analysis Of Listed Firms In Ghana. The Journal Of Risk Finance Vol. 6 No. 5, Pp. 438-445.As/Nzs. (2004). Risk Management Guidelines Companion To As/Nzs 4360:2004. Hb 436:2004. Standards Australia International, Sydney: Retrieved From Standards New Zealand Database.Brigham, E. F., & Houston, J. F. (2006). Dasar-Dasar Manajemen Keuangan. Diterjemahkan Oleh Ali Akbar Yulianto. Edisi Kesepuluh. Buku Kedua. Jakarta: Salemba Empat.Brigham, E. F., & Houston, J. F. (2011). Dasar-Dasar Manajemen Keuangan. Diterjemahkan Oleh: Ali Akbar Yulianto. Edisi Kesebelas. Buku Kedua. Jakarta: Salemba Empat.Deni Sunaryo, S. M. (2018). Pengaruh Leverage Operasional Dan Leverage Keuangan Terhadap Pengembalian Atas Ekuitas (ROE) Pada Sub Sektor Telekomunikasi Yang Terdaftar Di Bei Periode Tahun 2010-2017. Jurnal Saint Manajemen Volume 4 No. 1, 141-156.Elvira, C., & Hidayah, N. (2013). Pengaruh Corporate Social Responsibility, Leverage, Growth, Size Terhadap Return On Equity Pada Perusahaan Lq 45 Yang Tercatat Di Bursa Efek Indonesia Tahun 2009-2012. 49-61.Fahmi, I. (2014). Pengantar Manajemen Keuangan. Bandung: Alfabeta.Fitri, S. R., & Soelehan, A. (2014). Analisis Risiko Bisnis Dan Risiko Keuangan Terhadap Kemampulabaan Perusahaan (Study Kasus Pt. Merck, Tbk Dan Pt. Kimia Farma, Tbk).Gatsi, J. G., Gadzo, S. G., & Akoto, R. K. (2013). Degree Of Financial And Operating Leverage And Profitability Of Insurance Firms In Ghana. International Business And Management Vol. 7, No. 2, Pp. 57-65.Halim, A. (2015). Manajemen Keuangan Bisnis Konsep Dan Aplikasinya. Jakarta: Mitra Wacana Media.Hanafi, M. M., & Halim, A. (2016). Analisis Laporan Keuangan. Edisi Kelima. Yogyakarta: Upp Stim Ykpn.Hendra, A. (2009). Analisis Laporan Keuangan. Yogyakarta: Liberty.Hermuningsih, S. (2013). Pengaruh Profitabilitas, Growth Opportunity, Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Publik Di Indonesia. Bulletin Of Monetary Economics And Banking (Buletin Ekonomi Moneter Dan Perbankan), 16(2), 127-148.Hery. (2015). Analisis Laporan Keuangan. Edisi 1. Yogyakarta: Center For Academic Publishing Services.Horne, V., & Wachowicz. (2007). Fundamentals Of Financial Management, Prinsip-Prinsip Manajemen Keuangan. Jakarta: Salemba Empat.Husnan, S. (2010). Manajemen Keuangan Teori Dan Penerapan (Keputusan Jangka Panjang), Edisi Keempat. Yogyakarta: Bpfe.Jumingan. (2006). Analisis Laporan Keuangan. Jakarta: Pt. Bumi Aksara.Kaptiana, D. I., & Asandimitra, N. (2017). Pengaruh Struktur Modal, Risiko Bisnis, Dan Pertumbuhan Penjualan Terhadap Roe Perusahaan Manufaktur. Jurnal Bisnis Dan Manajemen Volume 6 No. 2, 122-129.Kasmir. (2008). Bank Dan Lembaga Keuangan Lainnya. Edisi Revisi 2008. Jakarta: Pt. Rajagrafindo Persada.Kasmir. (2017). Analisis Laporan Keuangan. Jakarta: Pt Rajagrafindo Persada.Kautsar, A. (2013). Analisis Pengaruh Firm Size, DER, Dan Sales Growth Terhadap Dividend Payout Ratio Dengan ROE Sebagai Variabel Intervening Pada Perusahaan Non Keuangan Yang Listed Di BEI Tahun 2009-2011. 1-16.Mappanyuki, R., & Sari, M. (2017). The Effect Of Sales Growth Ratio, Inventory Turn Over Ratio, Growth Opportunity To Companys Profitability (Survey In Indonesias Stocks Exchange). 8-16.Oriza, S., & Primadipta, L. (2012). Pengaruh Pajak Penghasilan, Beban Bunga, Depresiasi, Dan Kebijakan Dividen Terhadap Kebijakan Leverage Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2006-2010.S1 Thesis. Universitas Negeri Yogyakarta.Pantow, M. R., Murni, S., & Trang, I. (2015). Analisa Pertumbuhan Penjualan, Ukuran Perusahaan, Return On Asset, Dan Struktur Modal Terhadap Nilai Perusahaan Yang Tercatat Di Dalam Lq 45. Jurnal Riset Ekonomi, Manajemen, Bisnis Dan Akuntansi, 3(1). Hal 961-971.Pramana, T. (2011). Manajemen Risiko Bisnis. Jakarta: Sinar Ilmu.Puspitasari, N. D., Warmana, G. O., & Astiti, N. Y. (2020). Pengaruh Degree Of Financial Leverage Dan Degree Of Operating Leverage Terhadap Profitabilitas. Jurnal Widya Manajemen Vol. 2 (No. 1), Hal 28-35.Puspitasari, Y. (2015). Analisis Pengaruh Leverage Terhadap Profitabilitas Perusahaan Industri Makanan Yang Terdaftar Dalam Bursa Efek Indonesia.Putri, L., Bakri, S. A., & Bakar, S. W. (2017). Analisis Dol, Dfl Dan Dcl Terhadap Profitablitas Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2016. Jurnal Manajemen Dan Bisnis Sriwijaya Vol.15 (2), 95-105.Qurays, A. A., Susyanti, J., & Rachmat, A. (2017). Pengaruh Financial Leverage, Operating Leverage Dan Debt To Equity Ratio (DER) Terhadap Profitabilitas Perusahaan (Studi Kasus Perusahaan Asuransi Yang Terdaftar Di BEI Tahun 2012-2016). E Jurnal Riset Manajemen Prodi Manajemen, 36-50.Riyanto, B. (2010). Dasar-Dasar Pembelanjaan Perusahaan, Ed. 4. Yogyakarta: Bpfe.Rose, A. S., Randolf, W., Westerfield, & Jordan, B. D. (2000). Fundamentals Of Corporate Finance. Third Edition. Irwin Series In Finance. Irwin Inc.Sakti, G. (2019). Siaran Pers : Pariwisata Diproyeksikan Jadi Penyumbang Devisa Terbesar Lima Tahun Ke Depan. Jakarta: Kementerian Pariwisata Ri.Sartono, A. (2010). Manajemen Keuangan Teori Dan Aplikasi. Edisi 4. Yogyakarta: Bpfe.Susanto, R. K., & Purnamasari, L. (2016). Pengaruh Leverage Pada Profitabilitas (Industri Properti Dan Industri Otomotif Di Bursa Efek Indonesia). Stie Perbanas Surabaya, 1-15.Sutrisno. (2012). Manajemen Keuangan Teori, Konsep Dan Aplikasi. Yogyakarta: Ekonisia.Valentina, H., & Ruzikna. (2017). Pengaruh Struktur Modal, Risiko Bisnis, Dan Pertumbuhan Penjualan Pada Perusahaan Real Estate And Property Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2014. Jom Fisip Vol. 4 No. 2, 1-15.